Theoretical and Methodological Functions Media Influence on Adolescents - Jelena Maksimović; Zorica Stanisavljević Petrović (In Medias Res, 2014)
The study of the media and their relationship to changes in educational trends is very important and popular phenomenon. Today's youth live and grow up with the media as an integral part of their own socialization. The subject of the research is to study the theoretical and methodological influence of the media on adolescents. The research results confirmed the hypothesis that most adolescents use television and the Internet, to develop social media behaviors of adolescents and certain forms of antisocial behavior (violence, aggression), that young people want to look up to celebrities who are promoted by the media, that the physical inactivity of children increased due to greater exposure to the media, and social network (Facebook) has a negative role in the young (p <0,01).